Answer:
B
(x-2) is a factor since remainder is 0.
Step-by-step explanation:
We divide (x-2) into the polynomial [tex]-4x^4+6x^3+8x^2-6x-4[/tex] through long division or synthetic. We choose long division and look for what will multiply with (x-2) to make the polynomial [tex]-4x^4+6x^3+8x^2-6x-4[/tex] .
[tex](x-2)(-4x^3)=-4x^4+8x^3[/tex]
We subtract this from the original [tex]-4x^4-(-4x^4)+6x^3-(8x^3)+8x^2-6x-4[/tex].
This leaves [tex]-2x^3+8x^2-6x-4[/tex]. We repeat the step above.
[tex](x-2)(-2x^2)=-2x^3+4x^2[/tex].
We subtract this from [tex]-2x^3-(-2x^3)+8x^2-(4x^2)-6x-4=4x^2-6x-4[/tex]. We repeat the step above.
[tex](x-2)(4x)=4x^2-8x[/tex].
We subtract this from [tex]4x^2-(4x^2)-6x-(-8x)-4=2x-4[/tex]. We repeat the step above.
[tex](x-2)(2)=2x-4[/tex].
We subtract this from [tex]2x-(2x)-4-(4)=0[/tex]. There is no remainder. This means (x-2) is a factor.